DESIGN THINKING - Dekker, Teun den. ([S.l.] : ROUTLEDGE, 2021)
This book is not just for reading. Design Thinking is something you need to actually do. Reading about design thinking will increase your knowledge, but by doing it, you will learn what design thinking can mean for you, in your studies and your work. In this book we encourage you to take action: design thinking by doing. Since the end of the last millennium, design thinking has received an increasing amount of attention from the business community, social organizations, universities and colleges.Organizations are confronted with complex problems and issues that are no longer self-containe, clear or easy to define. Thecreative solutionstrategy offeredbydesign thinking appears to be increasingly needed to adequately respond to the questions, wishes and needs of customers and society as a whole. This bookunravels the thinking and working process of design thinking and offers practical tools for getting started. The author approaches design thinking in four chapters, from different perspectives: as a way of thinking, a way of working, a project approach and a tool box.Design thinking is a way of thinking answers the questions: How do design thinkers approach problems and challenges? Which six fundamental attitudes do they use and what do you need to know in order to use them? Design thinking is a way of working answers questions such as: What phases and milestones does the design process distinguish? What is the difference between the more structured design process and the messy' cycle of design thinking? Because you learn design thinking by doing, you will practice this in Design thinking is a project approach.Finally, in the last chapter Design thinking is a tool box, the methods and tools that you use in a design project will be discussed. This international edition of Design Thinking is written for students and workers who want to apply design thinking to tackle challenges, problems or complex (social) issues in a different, practical way within their own professional practice.
OCLC-licensed vendor bibliographic record.
Keywords: Product design; Creative ability; Critical thinking; BUSINESS & ECONOMICS / Management Science